Hubungan Status Nutrisi terhadap Fungsi Kognitif pada Pasien Hipertensi di Wilayah Kerja Puskesmas Silo, Jember - Rega Estu Kusumawati; Murtaqib Murtaqib; Kushariyadi Kushariyadi (Pustaka Kesehatan, 2021)
Hypertension is a condition characterized by an increase in blood pressure above 140/90mmHg. It can cause various complications, one of which is impaired cognitive function. Decreased cognitive function is influenced by nutritional status, if the nutrients brought to the brain are reduced, the brain's performance will also decrease. This study aims to determine the relation between nutritional status and cognitive function in hypertensive patients in the area of Silo ​Public Health Center, Jember Regency. This study used observational analytic with a cross-sectional design. With dependent variable is cognitive function and the independent variable is nutritional status. The total of sample are 91 patients. Sampling using non-probability sampling technique by purposive sampling. The instruments used in this study were tread scales, meters, and MMSE questionnaires. Data analysis was done using univariate analysis and bivariate analysis with spearmen correlation. The results of nutritional status checks found that 51 patients (56%) had normal. While the results of cognitive function examination obtained as many as 47 patients (51.6%) had normal cognitive function. The statistical test results with the Spearmen correlation showed that there is a relation between nutritional status and cognitive function in hypertensive patients with value of p= 0.002. There is a relation between nutritional status and cognitive function in hypertensive patients in the working area of ​Puskesmas Silo Jember regency.